2020
DOI: 10.1080/09602011.2020.1821718
|View full text |Cite
|
Sign up to set email alerts
|

Hebrew version of the Jansari assessment of Executive Functions for Children (JEF-C©): Translation, adaptation and validation

Abstract: The Jansari assessment of Executive Functions for Children (JEF-C ©) is a non-immersive computerized assessment of executive functions (EFs). This study aimed to create a cross-culturally adapted Hebrew version, JEF-C(H) © and to assess reliability and validity in the Israeli context. Forty typically developing Israeli children and adolescents, aged 11-18 years, were assessed with JEF-C(H) ©. In addition, participants and their parents filled in the Behaviour Rating Inventory of Executive Function (BRIEF). JEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Specifically, patients performed significantly worse on most of the JEF-C subscales and total scores, with 41.4% patients classified as having severe executive dysfunction (Gilboa et al, 2019 ). Recently, the same authors developed an adapted Hebrew version, JEF-C (H) and assessed reliability and validity in the Israeli context, involving typically developing Israeli children and adolescents (aged 11–18 years) (Orkin Simon et al, 2020 ). Overall, results showed the potential clinical utility of JEF-C (H) as a VR-based tool for an ecologically valid evaluation of executive functioning in Israeli children and adolescents.…”
Section: Virtual Reality Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, patients performed significantly worse on most of the JEF-C subscales and total scores, with 41.4% patients classified as having severe executive dysfunction (Gilboa et al, 2019 ). Recently, the same authors developed an adapted Hebrew version, JEF-C (H) and assessed reliability and validity in the Israeli context, involving typically developing Israeli children and adolescents (aged 11–18 years) (Orkin Simon et al, 2020 ). Overall, results showed the potential clinical utility of JEF-C (H) as a VR-based tool for an ecologically valid evaluation of executive functioning in Israeli children and adolescents.…”
Section: Virtual Reality Toolmentioning
confidence: 99%
“…Overall, results showed the potential clinical utility of JEF-C (H) as a VR-based tool for an ecologically valid evaluation of executive functioning in Israeli children and adolescents. Expressly, data indicated that JEF-C (H) showed interesting psychometric properties (e.g., acceptable internal consistency) for measuring EFs performance of young Israeli sample (Orkin Simon et al, 2020 ).…”
Section: Virtual Reality Toolmentioning
confidence: 99%
“…Interestingly, two of the articles that did not explicitly link EV to prediction of functioning (relying instead on participant feedback about the test’s face validity) nevertheless did examine the associations between test performance and functional outcome measures. Of these two, one did not find any associations between the outcome and the test of interest (Gilboa et al, 2019), and the other did find associations but referred to these as evidence of “concurrent validity” instead (Orkin Simon et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining seven articles (23%) did not rely on the prediction of functional outcomes as evidence of EV. Instead, three (10%) relied on appearance (i.e., verisimilitude), either alone (Orkin Simon et al, 2022) or in combination with tests’ associations with other measures (Doherty et al, 2015; Jovanovski et al, 2012); and four articles (13%) based their conclusions about EV on tests’ associations with other tests of EF (La Paglia et al, 2012, 2014; Raspelli et al, 2011), or a correlation between the virtual and the real versions of the same test (Laloyaux et al, 2014). Interestingly, three articles examined correlations between the test and functional outcome but did not link the results of these procedures to EV; instead, these articles used alternative “validity” terminology, referring to convergent (Gilboa et al, 2019; Kenworthy et al, 2020) and concurrent validity (Orkin Simon et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, wholly erroneous conceptualizations have also begun to emerge, conflating EV with sensitivity to brain injury (Torralva et al, 2012), tests’ ability to differentiate groups (Kallweit et al, 2020; Montgomery et al, 2010), or construct or concurrent validity evidenced by associations with other tests (Doherty et al, 2015; Jovanovski et al, 2012; La Paglia et al, 2012, 2014; Laloyaux et al, 2014; Raspelli et al, 2011). Importantly, for some authors, EV appears to have become completely decoupled from prediction of functional outcome, as some studies that examined the association between the test and functional outcome failed to draw any connection between their results and EV (Alderman et al, 2003; Chevignard et al, 2010; Chicchi Giglioli et al, 2021; Finnanger et al, 2022; Júlio et al, 2019; Laloyaux et al, 2014; Longaud-Valès et al, 2016; Moriyama et al, 2002; O’Shea et al, 2010; Oliveira et al, 2016; Orkin Simon et al, 2022; Verdejo-García & Pérez-García, 2007; Zartman et al, 2013). Notably, some authors even claimed evidence of EV in face of their own negative findings about veridicality (Chevignard et al, 2009; Clark et al, 2017; Gilboa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%